Metabolic disorders affecting the liver and heart: Therapeutic efficacy of miRNA-based therapies? - La Sala, Lucia (2024)
Liver and heart disease are major causes of death worldwide. It is known that metabolic alteration causing type 2 diabetes (T2D) and Nonalcoholic fatty liver (NAFLD) coupled with a derangement in lipid homeostasis, may exacerbate hepatic and cardiovascular diseases. Some pharmacological treatments can mitigate organ dysfunctions but the important side effects limit their efficacy leading often to deterioration of the tissues. It needs to develop new personalized treatment approaches and recent progresses of engineered RNA molecules are becoming increasingly viable as alternative treatments. This review outlines the current use of antisense oligonucleotides (ASOs), RNA interference (RNAi) and RNA genome editing as treatment for rare metabolic disorders. However, the potential for small non-coding RNAs to serve as therapeutic agents for liver and heart diseases is yet to be fully explored. Although miRNAs are recognized as biomarkers for many diseases, they are also capable of serving as drugs for medical intervention; several clinical trials are testing miRNAs as therapeutics for type 2 diabetes, nonalcoholic fatty liver as well as cardiac diseases. Recent advances in RNA-based therapeutics may potentially facilitate a novel application of miRNAs as agents and as druggable targets. In this work, we sought to summarize the advancement and advantages of miRNA selective therapy when compared to conventional drugs. In particular, we sought to emphasise druggable miRNAs, over ASOs or other RNA therapeutics or conventional drugs. Finally, we sought to address research questions related to efficacy, side-effects, and range of use of RNA therapeutics. Additionally, we covered hurdles and examined recent advances in the use of miRNA-based RNA therapy in metabolic disorders such as diabetes, liver, and heart diseases.